Antimicrobial Activity of Truncated and Polyvalent Peptides Derived from the FKCRRQWQWRMKKGLA Sequence against Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923 - Nataly de Jesús Huertas; Zuly Jenny Rivera Monroy; Ricardo Fierro Medina; Javier Eduardo García Castañeda (Molecules, 2017)
Peptides derived from LfcinB were designed and synthesized, and their antibacterial activity was tested against Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923. Specifically, a peptide library was constructed by systemically removing the flanking residues (N or C-terminal) of Lfcin 17–31 (17FKCRRWQWRMKKLGA31), maintaining in all peptides the 20RRWQWR25 sequence that corresponds to the minimal antimicrobial motif. For this research, also included were (i) a peptide containing an Ala instead of Cys ([Ala19]-LfcinB 17–31) and (ii) polyvalent peptides containing the RRWQWR sequence and a non-natural amino acid (aminocaproic acid). We established that the lineal peptides LfcinB 17–25 and LfcinB 17–26 exhibited the greatest activity against E. coli ATCC 25922 and S. aureus ATCC 25923, respectively. On the other hand, polyvalent peptides, a dimer and a tetramer, exhibited the greatest antibacterial activity, indicating that multiple copies of the sequence increase the activity. Our results suggest that the dimeric and tetrameric sequence forms potentiate the antibacterial activity of lineal sequences that have exhibited moderate antibacterial activity.